2013
DOI: 10.1590/s1415-790x2013000400007
|View full text |Cite
|
Sign up to set email alerts
|

Excessive daytime sleepiness in the elderly: association with cardiovascular risk, obesity and depression

Abstract: It was found that obesity for women, and depression and cardiovascular dysfunction risking for men were associated with EDS in the elderly. The variable sex is a confusion condition for the association with sleepiness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 29 publications
0
16
1
2
Order By: Relevance
“…The scale has been validated for older American women and has an adequate internal consistency (α = 0.76) 19 , In Brazil it has been validated for adults 18 and its feasibility was tested in institutionalized older people 20 , demonstrating that is possible use this instrument. Despite the limitations, this is a widely used scale for EDS assessment in older population 8,9,11,21,22 . Sociodemographic variables analyzed were: gender, age (grouped 65 -69, 70 -74, 75 -79 and 80 years and older), education level (0 -1, 1 -4, 5 -8, 9 years or more), and gross monthly family income (0 -1, 1 -3, 3 -5, 5 minimum wages and above).…”
Section: Methodsmentioning
confidence: 99%
“…The scale has been validated for older American women and has an adequate internal consistency (α = 0.76) 19 , In Brazil it has been validated for adults 18 and its feasibility was tested in institutionalized older people 20 , demonstrating that is possible use this instrument. Despite the limitations, this is a widely used scale for EDS assessment in older population 8,9,11,21,22 . Sociodemographic variables analyzed were: gender, age (grouped 65 -69, 70 -74, 75 -79 and 80 years and older), education level (0 -1, 1 -4, 5 -8, 9 years or more), and gross monthly family income (0 -1, 1 -3, 3 -5, 5 minimum wages and above).…”
Section: Methodsmentioning
confidence: 99%
“…Sleep disturbances are a hallmark of the depressive disorder, with approximately 80% of patients with depression complaining of a deterioration in the quantity and quality of sleep. 18 Lopes et al 36 also identified an association between depression and excessive daytime sleepiness, a manifestation of sleep dysfunction during wakefulness, and found that men with depression were more associated with this dysfunction.…”
Section: Sleep Characteristicmentioning
confidence: 97%
“…(24) The sedentary lifestyle in turn, may be associated with increased waist circumference and obesity, (19) increasing the chances of occurrence of these two risk factors and thus, of cardiovascular disease. A recent study with 168 elderly showed that waist circumference in men is associated with excessive daytime sleepiness, (25) illustrating how the relationships between these factors are intertwined. Thus, a sedentary lifestyle may contribute to the increased cardiovascular risk in various ways, since it is associated, to obesity, increased waist circumference, and excessive daytime sleepiness, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…(7) In another study, the increased BMI was associated with excessive daytime sleepiness in women but not in men, in which excessive daytime sleepiness was related, among other factors, to increased waist circumference. (25) …”
Section: Discussionmentioning
confidence: 99%